Peran Guru PAI dalam Meningkatkan Kesadaran Diri Siswa untuk Mencegah Perundungan di MA Al-Izzah Putra Kota Batu - Said, Ghiffari Syauqy; Rossidy, Imron (ISLAMIKA, 2024)
A surge in bullying cases is currently occurring among students and schools in various regions, currently boomeranging and going viral on Indonesian social media. This writing aims to explain, firstly to find out the role of PAI teachers in preventing bullying at school, secondly to find out teachers' strategies in preventing bullying at school. This research uses qualitative methods, the research subject is direct, the type of research carried out is field study. Data was collected through observation, interviews and documentation. To increase students' awareness of bullying, several efforts have been made including collaboration between teachers and school residents, speaking approaches to students, and strengthening students' morals. The strategies implemented include collaborating and collaborating with psychologists to discuss psychology, good communication with students' guardians to exchange information, inform each other about conditions and inform students about their condition. The PAI teacher's strategy is to find and find out the root of the problem of bullying, and provide moral and moral advice to students during morning assembly and open space for anyone who wants to report bullying. call victims and perpetrators of bullying to resolve problems that occur by mediating.